Hukum Menikah Dini Dan Dampaknya Bagi Pendidikan Anak - Ali Akbar (Consilium : Berkala Kajian Konseling dan Ilmu Keagamaan, 2020)
Ideally a person who is going to get married should have grown up both physically and thoughtfully for the sake of the realization of a harmonious, happy and prosperous couple, but many factors that cause early marriage include caused by excessive courtship and eventually pregnancy out of the wedlock or because of dependents his/her parents were too much so that their underage children were forced to mate to reduce their parents’ costs because there were still many siblings, or because their lives were so difficult that an underage child was married by his parents or the child was married to someone older but his life is well established so that it is expected from the marriage that it can help the economy of the family of the father and mother. The household is the first place for children to develop mental and personality formation which is than refined informal and non-formal education. Likewise the case with religious education must be started in the household as early as possible, such as the practice of prayer, fasting and others. Creating a religious atmosphere in the household not only makes the members of the household happy but also has a great influence on the formation of a religious human personality for the children.